Pelaksanaan Program Penanggulangan Kemiskinan Selama Pandemi Covid-19 di Kota Bukittinggi Sumatera Barat - Nabilla Nabilla; Roni Ekha Putera; Hendri Koeswara (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2022)
The problem of poverty will not stop to be discussed, the inequality of economic income conditions in society is no longer a trivial problem that can be ignored, because poverty is also a source of factors for other problems in people's lives. The government as an agent of public trust in managing the life of the state also strives to realize the goals of the state in terms of prosperity and welfare of the people, accordance goals of the Indonesian state in the Preamble 1945 Constitution in the fourth paragraph which reads ".... Protecting the entire Indonesian nation and the entire homeland of Indonesia to promote public welfare, educate the nation's life and participate in carrying out world order ..." . So in this case the government has determined poverty as one of the focuses in sustainable development, which is also based on international agreements that are currently stated in the Sustainable Development Goals (SDGs) which set poverty as the first goal in the focus of sustainable development. In this paper, the author will look at how the government manages the implementation of programs in poverty alleviation, especially during difficult times such as the current Covid-19 pandemic, because the state of the spread of this virus outbreak make impact on the life of the country, especially in terms of the country's economy. This research uses qualitative descriptive methods, with primary techniques data collection from interviews, and secondary data from related literature such as from scientific journals, e-books to other related government websitesKeywords: management program, poverty reduction, Covid-19, Bukittinggi City